2011
DOI: 10.1093/brain/awr142
|View full text |Cite
|
Sign up to set email alerts
|

The histone acetyltransferase p300 promotes intrinsic axonal regeneration

Abstract: Axonal regeneration and related functional recovery following axonal injury in the adult central nervous system are extremely limited, due to a lack of neuronal intrinsic competence and the presence of extrinsic inhibitory signals. As opposed to what occurs during nervous system development, a weak proregenerative gene expression programme contributes to the limited intrinsic capacity of adult injured central nervous system axons to regenerate. Here we show, in an optic nerve crush model of axonal injury, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
142
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 44 publications
9
142
2
1
Order By: Relevance
“…In support of our findings, p300/CBP has been shown to contribute to the survival, differentiation and neurite growth of a variety of neuronal cell types in the nervous system in vitro and in vivo (Chatterjee et al 2013;Chen et al 2010;Cong et al 2005;Culmsee et al 2003;Gaub et al 2011;Gaub et al 2010;Koyano-Nakagawa et al 1999;Lee et al 2009;Morikawa et al 2005;Rouaux et al 2003;Seo et al 2012;Sun et al 2001;Tsui et al 2014;Wang et al 2010;Wong et al 2005). In terms of the development of midbrain DA neurons, which progressively degenerate in PD, there is evidence to suggest that p300/CBP contributes to the acquisition of a DA phenotype in differentiating neurons (Seo et al 2012).…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of supporting
confidence: 84%
See 1 more Smart Citation
“…In support of our findings, p300/CBP has been shown to contribute to the survival, differentiation and neurite growth of a variety of neuronal cell types in the nervous system in vitro and in vivo (Chatterjee et al 2013;Chen et al 2010;Cong et al 2005;Culmsee et al 2003;Gaub et al 2011;Gaub et al 2010;Koyano-Nakagawa et al 1999;Lee et al 2009;Morikawa et al 2005;Rouaux et al 2003;Seo et al 2012;Sun et al 2001;Tsui et al 2014;Wang et al 2010;Wong et al 2005). In terms of the development of midbrain DA neurons, which progressively degenerate in PD, there is evidence to suggest that p300/CBP contributes to the acquisition of a DA phenotype in differentiating neurons (Seo et al 2012).…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of supporting
confidence: 84%
“…This is an important finding considering the limited number of HAT activators which have been produced (Schneider et al 2013), and the corresponding paucity of studies investigating their neurotrophic potential. The ability of p300/CBP activity to promote neurite growth has been reported in other neuronal populations (Gaub et al 2011;Gaub et al 2010;Lee et al 2009), while small molecule-mediated activation of p300/CBP promotes the growth of neurons in the adult mouse dentate gyrus in vivo (Chatterjee et al 2013). …”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of mentioning
confidence: 84%
“…While our work here describes that specific epigenetic codes are induced endogenously following a conditioning lesion that leads to CNS regeneration, it is also consistent with previous findings from our laboratory that showed the presence of a transcriptional complex formed by p53, p300 and PCAF in the proximity of several RAGs including GAP-43, Coronin 1b and Rab13 in primary neurones as well as facial motor neurones in a PNS facial nerve axotomy model [34][35][36] . Additionally, we found that the histone acetyltransferase p300 (which may form a complex with PCAF) is developmentally regulated in retinal ganglion cells and whose overexpression drives axonal regeneration of the injured optic nerve 33 .…”
Section: Discussionmentioning
confidence: 91%
“…It has been hypothesized that merely shifting the balance from a deacetylated to a globally acetylated chromatin environment by inhibition of HDACs could recapitulate the conditioning lesion and could lead to regeneration. However, recent experimental evidence 32 and our own work using HDAC class I and HDAC class I and II inhibitors 33 has proven this to be insufficient in producing postlesion regeneration of sensory fibres following a spinal or optic nerve injury and therefore unlikely the key to unlocking the molecular mechanisms of regeneration. While our work here describes that specific epigenetic codes are induced endogenously following a conditioning lesion that leads to CNS regeneration, it is also consistent with previous findings from our laboratory that showed the presence of a transcriptional complex formed by p53, p300 and PCAF in the proximity of several RAGs including GAP-43, Coronin 1b and Rab13 in primary neurones as well as facial motor neurones in a PNS facial nerve axotomy model [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CBP was shown to ameliorate learning and memory deficits in a mouse AD model by increasing brain derived neurotropic factor (BDNF) 38 while p300 but not HDAC inhibitors was found to promote axonal regeneration by inducing axonal outgrowth genes. 83 It is important to consider that modulation of specific HAT levels and/or activity might epigenetically reprogram multiple specific genes that function together to produce a neuroprotective effect, as suggested by our ChIP-Seq analysis for Tip60. 7,34 Therefore, it will be critical to identity the full array of these genes to further dissect their neuroprotective nature for more effective design of specific HAT based therapeutic strategies.…”
mentioning
confidence: 99%